Medical and biological feasibility of the recipe for baby boiled sausages for feeding children with food intolerance - A. V. Zykova; A. M. Patieva; Z. N. Khatko; S. V. Patieva (Новые технологии)
As a result of the conducted scientific research, the use of raw materials with low allergenic activity has been justified for the development of a recipe for boiled sausages for feeding children suffering from food intolerance. The experimental work was carried out on the base of KubSAU named after. I.T. Trubilin. According to the research design, biotechnological requirements for the composition and quality of the products have been analyzed, intended for a group of young children. The basic quality requirements are shown to ensure the safety of baby sausages for feeding children from 1.5 years of age: protein content – no less than 12 g, fat – no more than 18 g, salt – no more than 1.5 g and others. The selection and assessment of the quality characteristics of raw materials with low allergenic characteristics, which can be used as part of a new formulation, have been carried out. Based on the data obtained a meat-based product for children over 1.5 years old has been formulated in the form of boiled sausages intended for children with food intolerance. A model of a recipe composition with specified quality characteristics has been developed, including turkey, pork, horse meat, corn flour, goat milk, zucchini, and parsley. Pilot batch of sausages has been developed with subsequent assessment of the nutritional and biological value of the recipe model for feeding children with food intolerance, which shows high characteristics of the new product. The daily satisfaction of young children in basic nutrients has been studied. The developed boiled sausage product meets the requirements for protein (13.23 g) and fat (16.36 g) content.